PENCARIAN DANA MASJID DI JALAN RAYA DALAM PERSPEKTIF HUKUM ISLÂM - Moch Cholid Wardi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2008)
This article aims to describe the activity of street organizing donation (an activity of organizing a donation done on the street or highway) from Islamic law perspective. This activity arises a contradiction, there has been a side support it but another side that reject it. They argue to each other to defend their own opinion. As a result, an Islamic law perspective looks urgent to ensure whether that activity is legal. The Islamic law enforcement against the argue must regard some basic grounds including geographic, social-cultural, economic motives as well as certain vertical ones. Moreover, it has to anticipate its impact on Islamic society generally and the priority of advantages better than its mafsadat. In fact, street organizing donation could come up madlarah as it looks the act of begging that is forbidden in Islam, universally decrease Muslims dignity, unclear law of share on the money gained. Last but not least, the concept of mosque building is not categorized dlarûrah.